2018
DOI: 10.1155/2018/8740284
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Responses to Acupuncture at GV24 and Bilateral GB13 in Rat Models of Alzheimer’s Disease

Abstract: Acupuncture has been widely used in China to treat neurological diseases including Alzheimer's disease (AD). However, its mechanism remains unclear. In the present study, eighty healthy Wistar rats were divided into a normal control group (n = 15) and premodel group (n = 65). Forty-five rats that met the criteria for the AD model were then randomly divided into the model group (MG), the nonacupoint group (NG), and the acupoint group (AG). All rats received positron emission tomography (PET) scanning, and the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 70 publications
0
12
0
Order By: Relevance
“…But there is no research directly compared the combination of these two modeling methods with use of them individually. Although our previous findings demonstrated that the intrahippocampal injection of Aβ1-40 combining intraperitoneal injection of D-gal did successfully simulate Alzheimer’s disease-like behavior changes [ 13 , 23 ], but we cannot distinguish which modeling method contributed more to the change of the Aβ and p-tau level in the brain as well as cognitive dysfunctions in behavior test.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…But there is no research directly compared the combination of these two modeling methods with use of them individually. Although our previous findings demonstrated that the intrahippocampal injection of Aβ1-40 combining intraperitoneal injection of D-gal did successfully simulate Alzheimer’s disease-like behavior changes [ 13 , 23 ], but we cannot distinguish which modeling method contributed more to the change of the Aβ and p-tau level in the brain as well as cognitive dysfunctions in behavior test.…”
Section: Discussionmentioning
confidence: 92%
“…1 b) or at nonacupoints (nonacupoint group) by the same acupuncturist. The electroacupuncture and nonacupoint locations were the same as those reported in our previous study [ 13 ]. Sterilized stainless disposable needles (25 mm in length, 0.35 mm in diameter; Suzhou Medical Appliance Factory, China) were inserted 2 mm into the GV24 and bilateral GB13 acupoints or the nonacupoints and then connected to an electronic acupuncture treatment instrument (Hans Acupoint Nerve Stimulator 200E, Nanjing Jisheng Medical Technology Co., Ltd., China).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The white matter abnormality may result in the decreased functional connectivity or the rearrangement of local cognitive networks. Previous studies prove that these functional networks could be considered neuroimaging evidence of acupuncture effects on cognitive function ( Dhond et al, 2008 ; Qiu et al, 2010 ; Cui et al, 2018 ; Wen et al, 2018 ). Therefore, future studies aiming at structure and function changes and their interaction will help uncover the mechanism of acupuncture.…”
Section: Discussionmentioning
confidence: 97%
“…As a consequence, glucose metabolism is especially important for maintaining the normal function of the brain, especially cognitive-related functions. Acupuncture improved the learning and memory abilities of AD rats by needling GV24 and bilateral GB13 acupoints (Cui et al, 2018). Furthermore, positron emission tomography (PET) study showed that acupuncture by needling in AD rats could significantly increase the rate of glucose metabolism in the hypothalamus, thalamus, and brain stem.…”
Section: Alzheimer’s Diseasementioning
confidence: 99%